Sustainable Marketing Schemes for Micro, Small, and Medium Enterprise (MSME) Owners Operating in Mabolo, Cebu City - Simbajon, Leona Jane P.; Villacarillo, Shyr G.; Selim, John Carl B.; Viking, Kent Ivan A.; Polinar, Mark Anthony N.; Mahipos, April Marie N.; Ato, Joanna Marie U. (Transpublika Publisher, 2025)
Sustainable marketing strategies play a vital role in helping multinational companies balance sustainability and profitability. However, local studies investigating micro, small, and medium enterprises’ (MSMEs) understanding, adoption, or implementation of these strategies at the barangay level were underexplored. This descriptive-correlational study examined the correlation between the importance and the effectiveness of sustainable marketing practices among micro, small, and medium enterprises (MSMEs) owners operating in Mabolo, Cebu City. The study drew 240 respondents from a population of 633 using Raosoft, an online sample size calculator, and selected them randomly to participate in data gathering. The authors utilized an adapted tool to gather data from the respondents. Frequency count, weighted mean, and Pearson correlation were used in the data analysis. Based on the study’s results, the interpretation of the correlation between the level of importance and the level of effectiveness implemented by MSME owners showed positive and strong results. Also, it was found that MSMEs place greater importance on sustainable marketing strategies, and their effectiveness in implementing them also tends to increase. A green marketing framework was recommended to address the lack of importance, as it helps MSME owners improve their sustainable marketing strategies.